Hippocampal Long-Term Depression in the Presence of Calcium-Permeable AMPA Receptors - Cao, Feng; Zhou, Zikai; Cai, Sammy; Xie, Wei; Jia, Zhengping (Frontiers in Synaptic Neuroscience, 2018)
The GluA2 subunit of AMPA glutamate receptors (AMPARs) has been shown to be critical for the expression of NMDA receptor (NMDAR)-dependent long-term depression (LTD). However, in young GluA2 knockout (KO) mice, this form of LTD can still be induced in the hippocampus, suggesting that LTD mechanisms may be modified in the presence of GluA2-lacking, Ca2+ permeable AMPARs. In this study, we examined LTD at the CA1 synapse in GluA2 KO mice by using several well-established inhibitory peptides known to block LTD in wild type rodents. We showed that while LTD in the KO mice is still blocked by the PICK1 peptide pepEVKI, it becomes insensitive to the NSF peptide pep2m. In addition, the effects of actin and cofilin inhibitory peptides were also altered. These results indicate that in the absence of GluA2, LTD expression mechanisms are different from those in wild type animals, suggesting that there are multiple molecular processes enabling LTD expression that are adaptable to physiological and genetic manipulations.